Inhibitory Role of Growth Hormone in the Induction and Progression Phases of Collagen-Induced Arthritis - Villares, Ricardo; Criado, Gabriel; Juarranz, Yasmina; Lopez-Santalla, Mercedes; García-Cuesta, Eva M.; Rodríguez-Frade, José M.; Leceta, Javier; Lucas, Pilar; Pablos, José Luis; Martínez-A, Carlos; Garin, Marina I.; Gomariz, Rosa P.; et al. (Frontiers in Immunology, 2018)
Evidence indicates an intimate connection between the neuroendocrine and the immune systems. A number of in vitro and in vivo studies have demonstrated growth hormone (GH) involvement in immune regulation. The GH receptor is expressed by several leukocyte subpopulations, and GH modulates immune cell proliferation and activity. Here we found that sustained GH expression protected against collagen-induced arthritis (CIA); in GH-transgenic C57BL/6 (GHTg) mice, disease onset was delayed and its overall severity was decreased. The anti-collagen response was impaired in these mice, as were inflammatory cytokine levels. Compared to control arthritic littermates, immunized GHTg mice showed significantly lower RORt (retinoic acid receptor-related orphan receptor gamma 2), IL-17, GM-CSF, IL-22 and IFN mRNA expression in draining lymph nodes, whereas there were no differences in IL-21, IL-6 or IL-2 mRNA levels. Data thus suggest that Th17/Th1 cell plasticity toward a pathological phenotype is reduced in these mice. Exogenous GH administration in arthritic DBA/1J mice reduced the severity of established CIA as well as the inflammatory environment, which also shows a GH effect on arthritis progression. These results indicate that GH prevents inflammatory joint destruction in CIA. Our findings demonstrate a modulatory GH role in immune system function that contributes to alleviating CIA symptoms, and underlines the importance of endocrine regulation of the immune response.